Effect of saline water on soil salinity and on water stress, growth, and yield of wheat and potatoes - van Hoorn I.W.; Katerji N.; Hamdy A.; Mastrorilli M. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
Wheat and potatoes were grown in tanks filled with loam and clay and irrigated with water of three different levels of salinity and, for the wheat, with two irrigation regimes. A combination of soil water sampling and salt balance was used to study the development of soil salinity and the composition of the soil water. This revealed and increase in absorbed sodium, a decrease in absorbed calcium and magnesium, and precipitation of a mixture of calcium and magnesium carbonate. Predawn leaf-water potential and stomatal conductance can be used as parameters for water stress, and show good coherence with growth and yield. That potatoes are more sensitive to water stress than wheat was reflected by greater differences in leaf-water potential and stomatal conductance, and a more severe yield de-crease. Soil, salinity and water regime affect water stress, growth, and yield. The water efficiency of wheat and potatoes was not affected by soil and salinity.